Altered Functional Connectivity of Striatal Subregions in Patients with Multiple Sclerosis - Cui, Fangyuan; Zhou, Li; Wang, Zengjian; Lang, Courtney; Park, Joel; Tan, Zhongjian; Yu, Yao; Sun, Chunyan; Gao, Ying; Kong, Jian (Frontiers in Neurology, 2017)
Abnormal corticostriatal resting-state functional connectivity (rsFC) has been implicated in the neuropathology of multiple sclerosis (MS). As a component of the basal ganglia, the striatum is involved in diverse functions including movement, cognition, emotion and limbic information processing. However, the brain circuits of the striatal subregions contributing to the changes in rsFC in RRMS patients remain unknown. As individual striatal subregions are believed to be connected to specific functional cortical networks, we used six subdivisions of the striatum in each hemisphere as seeds to investigate the rsFC of striatal subregions between relapsing-remitting multiple sclerosis (RRMS) patients and matched healthy controls. In addition, we also scanned a subcohort of RRMS patients after an average of seven months to test the reliability of our findings. Compared to healthy controls, we found significantly increased dorsal caudal putamen (DCP) connectivity with the premotor area, dorsal lateral prefrontal cortex (DLPFC), insula, precuneus and superior parietal lobule and significantly increased connectivity between the superior ventral striatum (VSs) and posterior cingulated cortex (PCC) in RRMS patients of both scans. Furthermore, we found significant associations between the Expanded Disability Status Scale (EDSS) and the rsFC of the left DCP with the DLPFC and parietal areas in RRMS patients. Our results suggest that the DCP may be a critical striatal subregion in the pathophysiology of RRMS.